Hipertensión arterial en los adultos mayores de 60 años del cantón Zapotillo, en el periodo mayo-octubre del 2015. - Porres Gonzaga, Jefferson Kennedy (2016)
Hypertension is a disease and cardiovascular risk factor whose diagnosis is established by simple numerical variable although it has proven to be a multifactorial syndrome that causes systemic changes, complications and death. Hypertension is a factor highly prevalent cardiovascular risk in the world and particularly overwhelming in low- and middle-income countries. The President of the Ecuadorian Society of Cardiology , Dr. Santiago Garcia explains that the high prevalence of cardiovascular disease is marked by six risk factors: snuff , high blood pressure , diabetes , high cholesterol , obesity , psychosocial factors ( levels stress) and the absence of protective factors : proper exercise and daily intake of fruits and vegetables. This research aims to determine the prevalence of hypertension in adults over 60 years and identify the main risk factors associated with its development. It is performed under a quantitative approach, transverse and descriptive. The survey, consisting of 16 items, which assess and determine the main risk factors associated with its development, is used if people are hypertensive. The sample analyzed is clear of all adults over 60 years the canton Zapotillo during the period May to October 2015, chosen according to certain criteria for inclusion. The total sample is 164 patients female and male. Regarding the results, they noted that of 164 people found that 117 is 71.34 % of people over age 60 are hypertensive and 47 is 28.66 are no hypertensive. It is the main factors: smoking, physical inactivity, alcohol consumption, stress, diet hipersódica Keywords: Hypertension, risk factors, prevalence.